Constructed wetlands for wastewater treatment in Europe (Backhuys Publishers, 1998)
The content of indivudual chapters is usually divided into following sections: history of the use of constructed wetlands in a particular country, types of constructed wetlands, main dessign parameters, treatment efficiency,...